Alcohol, No Ordinary Commodity: policy implications for Canada - Jean-François Crépault; Jean-François Crépault; Timothy S. Naimi; Timothy S. Naimi; Jürgen Rehm; Jürgen Rehm; Jürgen Rehm; Jürgen Rehm; Jürgen Rehm; Jürgen Rehm; Kevin D. Shield; Kevin D. Shield; et al. (Frontiers Media S.A., 2024)
Alcohol is a favorite psychoactive substance of Canadians. It is also a leading risk factor for death and disability, playing a causal role in a broad spectrum of health and social issues. Alcohol: No Ordinary Commodity is a collaborative, integrative review of the scientific literature. This paper describes the epidemiology of alcohol use and current state of alcohol policy in Canada, best practices in policy identified by the third edition of Alcohol: No Ordinary Commodity, and the implications for the development of effective alcohol policy in Canada. Best practices - strongly supported by the evidence, highly effective in reducing harm, and relatively low-cost to implement - have been identified. Measures that control affordability, limit availability, and restrict marketing would reduce population levels of alcohol consumption and the burden of disease attributable to it.